Child Abuse in Meg Elison’s Find Layla - Dinda Novia Alfareza; Y. B. Agung Prasaja (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This study discusses child abuse in Meg Elison’s Find Layla. The purpose of this study is to describe the forms, character objectification, causes and effects of child abuse experienced by Layla and Andy. The research method used is descriptive qualitative method. This study uses a psychological approach. The psychoanalysis is used to evaluate the characters in the novel. Sue & Chamberline’s four domains of child abuse causes are used in this study. Martha Nussabaum’s objectification theory is used to analyze in what ways the abuser objectifies the child. Joyce Shannon’s theory of violence against children is also used in this study to determine the impact of child abuse in the novel. There are four forms of violence experienced by Layla and Andy: neglect, physical abuse, psychological abuse and sexual abuse. Darlene’s objectification of the child abuse is shown by treating her child as an object. It is found that there are two ways that Darlene objectifies her child, namely violability and denial of subjectivity. There are three causes of Darlene’s child abuse: divorce, past childhood experiences, and mental illness. The impact of child abuse experienced by Layla and Andy is physical and psychological. The physical impact of child abuse experienced by Layla and Andy is malnutrition. The psychological impact experienced by Layla is anxiety disorder and Andy has post traumatic stress disorder. Andy also experience difficulties in language and speech.